6-34d=-3

Combine d and 34.

6-d⋅34=-3

Move 3 to the left of d.

6-3d4=-3

6-3d4=-3

Subtract 6 from both sides of the equation.

-3d4=-3-6

Subtract 6 from -3.

-3d4=-9

-3d4=-9

Multiply both sides of the equation by -43.

-43⋅(-3d4)=-43⋅-9

Simplify -43⋅(-3d4).

Cancel the common factor of 4.

Move the leading negative in -43 into the numerator.

-43⋅(-3d4)=-43⋅-9

Move the leading negative in -3d4 into the numerator.

-43⋅-3d4=-43⋅-9

Factor 4 out of -4.

4(-1)3⋅-3d4=-43⋅-9

Cancel the common factor.

4⋅-13⋅-3d4=-43⋅-9

Rewrite the expression.

-13⋅(-3d)=-43⋅-9

-13⋅(-3d)=-43⋅-9

Cancel the common factor of 3.

Factor 3 out of -3d.

-13⋅(3(-d))=-43⋅-9

Cancel the common factor.

-13⋅(3(-d))=-43⋅-9

Rewrite the expression.

-1⋅(-d)=-43⋅-9

-1⋅(-d)=-43⋅-9

Multiply.

Multiply -1 by -1.

1⋅d=-43⋅-9

Multiply d by 1.

d=-43⋅-9

d=-43⋅-9

d=-43⋅-9

Simplify -43⋅-9.

Cancel the common factor of 3.

Move the leading negative in -43 into the numerator.

d=-43⋅-9

Factor 3 out of -9.

d=-43⋅(3(-3))

Cancel the common factor.

d=-43⋅(3⋅-3)

Rewrite the expression.

d=-4⋅-3

d=-4⋅-3

Multiply -4 by -3.

d=12

d=12

d=12

Solve for d 6-3/4d=-3